Efeitos de inseticidas e acaricidas na sobrevivência e reprodução do predador Ceraeochrysa cubana (Hagen, 1861)(Neuroptera, Chrysopidae) em laboratório - Mattioli, Eli (1992)
The objective of this work was to study and evaluate the physiological selectivity of some acaricides and insecticides on eggs, early stage larvae and adults of Ceraeochysa cubana (Hagen, 1861)(Neuroptera, Chrysopidae), as well as the primary effects of these supposedly selective compounds on fertility and fecundity during the adult stage. The trials were carried out in the Biology Laboratory of Insects at ESAL (Escola Superior de Agricultura de Lavras), an agricultural college in Lavras, Minas Gerais, Brazil. They were carried out under the following conditions: temperature, 25 + 2°C; relative humidity, 70 + 10%; and photophase 12 hours. Adult insects were collected from ESAL's citrus orchards in order to make up the samples for the trails. The compounds which were diluted in distilled water were sprayed with a maximum dosage recommended for field applications by using the Potter Tower for 20 seconds. In the case of the eggs, it was also employed the immersion application technique for 5 seconds. The results showed that the egg stage demonstrated a high tolerance to all compounds tested, independent of the application method used. The alfacypermethrin and cyfluthrin pirethroids compounds prolonged the egg incubation period, while the chemical residues of the cyfluthrin and deltamethrin compounds caused negative effects on the neonate larvae. The first stage larvae of C. cubana showed a relatively higher tolerance to piretroids than the adult insects. The larvae were highly susceptible to the diflubenzuron and flufenoxeron compounds (growth regulators), which inhibited the ecdysis process in 100% of the cases. These compounds caused no lethal effect on the adult stage. Regarding mortality, both the fenbutatin oxide and quinomethionate acaricides and the Bacillus thuringiesis Berliner microbial insecticide were harmless to both the larvae and adults. Cyfluthrin and deltamethrin were extremely harmful and killed 100% of the adult sampling, while 20% resisted the alfacypermethrin. Concerning the primary effects on reproductive capability of C. cubana, it was observed that alfacypermethrin and pirimicarb affected the females reproduction, thus reducing significantly the daily capacity of oviposition; nevertheless, they did not affect the progenesis viability. Quinomethionate influenced negatively the reproductive mechanism of the adult insects and was responsible for the inhibition of 50% of the eggs fertility, and also caused anomalies like fragility and atrophy of the pedicel. However, it did not interfere with egg production capacity of the female. On the other hand, diflubenzuron and flufenoxuron inhibited the viability of egg production capacity by 100% in such away that it became irreversible, with a high percentage of inviable eggs (96.32% and 88.43% respectively). They also affected the females' reproduction by reducing the daily capacity of oviposition to 50%. According to the analysis, the cyfluthrin, deltamethrin, diflubezuron and flufenoxuron compounds were considered highly harmful; alfacypermethrin, pirimicarb and quinomethionate were of intermediate harmfulness, while fenbutathion oxide and B. thuringiensis were harmless to the various stage of the C. cubana life cycle in laboratory conditions.